Problematika Pembelajaran Bahasa Arab di Madrasah Aliyah Negeri 2 Model Medan - Suryadi Nasution (Universitas Yudharta Pasuruan, 2021)
This study aims at describing the problems and abilities of MAN 2 Model students in Medan Helvetia in using Arabic. These problems are analysed based on the students’ ability in Muhadatsah and Qawaid. The study employed mixed research method with descriptive and presentative data analysis. The results showed that in regard to Muhadatsah, Arabic learning activities at MAN 2 Model have a fairly low standard since the students do not have a habit of using Arabic in the school environment so that students are unable to speak Arabic actively dan fluently. Meanwhile, in terms of Qawaid mastery, the students are not provided with systematic materials in learning the rules of Arabic (nahwu-sharaf). The only Arabic learning media relies on textbooks given to the students.